(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the emergence of the theory of convergence in linguistics, the convergence of syntactic-stylistic means of artistic or poetic speech with syntactic-stylistic figures and stylistic changes in the structure of speech, as well as the influence of speech on the artistic and aesthetic function of speech. speech, the article examines intermediate structural features of glottogonic convergence in several languages (related or unrelated), the formation of features (for example, contracts), structural-diachronic convergence - a historical process that means a decrease in diversity. In the linguistic system, as a result of the loss of some variational differences, there is the existence of features (motifs) called substratum, superstrate and abstract, which are the basis of convergence in linguistics; the term convergence must be understood as a complex stylistic structure. a method created as a result of the use of syntactic-stylistic means of different levels for the emergence of a single stylistic goal, the emergence of various forms of rapprochement between them as a result of the mutual use of syntactic-stylistic means, the most important syntactic - the fact that polysyndeton, which is considered a stylistic figure, has the same peculiarity. According to the observed linguistic facts, the use of polysyndeton in poetic speech, together with more structural parallelism, gradation, antithesis and rhetorical devices of questions, leads to the formation of various forms of convergence, determining the artistic and aesthetic function and effectiveness of poetic or artistic speech, and the results of a study of a high level of expressiveness and imagery.